Mathematical modeling and analysis of the development of territorial communities - Bihun, Roman; Lytvyn, Vasyl; Oleksiv, Nazar (Technology audit and production reserves, 2021)
This article examines the problems of the development of united territorial communities, in particular, unemployment and economic problems. The object of the research is the improvement of territorial communities on the example of the Lviv region (Ukraine). One of the most problematic areas is the fact that communities, in most cases, do not have enough funds to solve economic and other problems. The study uses the idea of the need to create self-sufficient communities with a sufficient number of financial instruments for their own development. The mathematical model of the decision support system for the development of territorial communities using the agro-industrial sector is also considered. An important step in building a mathematical model of the agro-industrial complex is taking into account the specifics of agriculture. The paper considers a mathematical model of linear and multifactorial regression, which describes the relationship between the amount of resources expended and the volume of output. Since the processes in the economy and production processes in agriculture are complex, it is difficult to describe them using only linear deterministic models. A common case is when task variables take some discrete values or values from a specific one. This situation makes the search difficult. To build a mathematical model for the development of territorial communities and study the fact that the development of agro-industry will improve the overall economic situation of the territorial community, correlation and regression analysis, the Farrar-Glauber method and the method of least squares are used. Thanks to the listed instruments, the statement is formed that the regulation of key factors of economic indicators of the agricultural sector can positively affect the growth of the economic component of territorial communities. The created mathematical model clearly forms the conclusion that agriculture in local communities can become an economic engine of community development, taking into account regional conditions.